2020
DOI: 10.36076/ppj.2020/23/e185
|View full text |Cite
|
Sign up to set email alerts
|

hole-Course Application of Dexmedetomidine Combined with Ketorolac in Nonnarcotic Postoperative Analgesia for Patients with Lung Cancer Undergoing Thoracoscopic Surgery: A Randomized Control Trial

Abstract: BACKGROUND: Opioid-based postoperative analgesia provides adequate analgesia with much adverse effects and immunosuppression. Dexmedetomidine and ketorolac have properties of opioid-sparing, antiinflammation, and immune protection. OBJECTIVES: To investigate the efficacy and safety of whole-course application of dexmedetomidine combined with ketorolac in nonnarcotic postoperative analgesia and its effect on inflammatory response and immune function in thoracoscopic surgery of lung cancer. STUDY DESIGN: Doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Therefore, we implemented a combination of MINB and non-opioid analgesic adjuvants to achieve a potential opioid-sparing effect. Compared to the traditional intercostal block-based approach, 6 this novel opioid-sparing strategy prolonged the time to first request of analgesia, with lower PCIA pressing times and rescue analgesia, which may benefit from the opioid-sparing effect of MINB by extending 24 h after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we implemented a combination of MINB and non-opioid analgesic adjuvants to achieve a potential opioid-sparing effect. Compared to the traditional intercostal block-based approach, 6 this novel opioid-sparing strategy prolonged the time to first request of analgesia, with lower PCIA pressing times and rescue analgesia, which may benefit from the opioid-sparing effect of MINB by extending 24 h after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine (DEX) and NSAIDs were recommended for postoperative analgesia to reduce opioid consumption. 4 , 5 The whole-course application of DEX combined with ketorolac 6 has been demonstrated to provide adequate and safe postoperative intravenous patient-controlled analgesia (PCIA) following thoracoscopic surgery. Based on the above, a novel opioid-sparing analgesia that combined with MINB and dexmedetomidine, as well as NSAIDs, was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Shim and colleagues reported that intraoperative intravenous dexmedetomidine and ketorolac improved postoperative analgesia after robotic-assisted laparoscopic radical prostatectomy in patients who received rectus sheath block, and significantly decreased opioid requirement during the 24 h after surgery [21]. Wen and colleagues reported that compared with sufentanil-based analgesia for thoracoscopic surgery, dexmedetomidine combined with ketorolac in non-narcotic postoperative analgesia provided adequate and safe postoperative analgesia and reduced sufentanil consumption, analgesic-related complications, inflammation, and immunosuppression [22].…”
Section: Discussionmentioning
confidence: 99%
“… 50 Furthermore, Guo et al found that 1 μg/kg dexmedetomidine pumped intravenously for 10 min as a loading dose and maintained at 0.4 μg/(kg·h) until 30 min before the end of lung cancer operation reduced the TNF-α level of patients, 51 which was also reported by other studies with different dexmedetomidine infusion rates. 52 Moreover, dexmedetomidine infusion could also promote CD3+ and CD4+ levels and CD4+/CD8+ ratio and decrease IL-6 levels in lung cancer operation 6 , 53–56 compared with the control. Patients pumped with 0.5 μg/kg dexmedetomidine intravenously for 15 min as a loading dose and maintained at 0.4 μg/(kg·h) until the end of oral cancer operation had elevated CD3+ and CD4+ levels and CD4+/CD8+ ratio.…”
Section: The Role Of Dexmedetomidine In Indirect Tumor-progressive Fa...mentioning
confidence: 96%